2008
DOI: 10.1021/es8022336
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Brominated Flame Retardants: Are They a Relevant Source of Emerging Brominated Aromatic Compounds in the Environment?

Abstract: A purge and trap method was used to study the release of brominated organic compounds from polymeric brominated flame retardants (BFRs), a relatively unknown class of flame retardant materials. Among the volatile brominated organics released, pentabromotoluene (PBTo), pentabromoethylbenzene (PBEB), and hexabromobenzene (HBB) were of particular interest because of their high potential to persist in the environment The impact of a thermal stress on the release of these compounds was assessed by applying differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 25 publications
3
58
2
Order By: Relevance
“…HBBz was detected at low levels (0.02-0.09 pg/m 3 ) in four outdoor air samples collected at a rural/suburban location in Canada in 2005 [67]. A low concentration of HBBz (0.48 ng/g dw) was also found in a sample of outdoor dust (from atmospheric deposition) in Germany [68].…”
Section: Abiotic Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…HBBz was detected at low levels (0.02-0.09 pg/m 3 ) in four outdoor air samples collected at a rural/suburban location in Canada in 2005 [67]. A low concentration of HBBz (0.48 ng/g dw) was also found in a sample of outdoor dust (from atmospheric deposition) in Germany [68].…”
Section: Abiotic Samplesmentioning
confidence: 99%
“…Polymeric BFRs could be possible sources of volatile brominated compounds even at low thermal stress. HBBz and other volatile brominated organics were released from a pentabromobenzyl acrylate oligomer (FR-1025, ICL Industrial Products, formerly Dead Sea Bromine Group, Israel) at room temperature [67]. The release rate increased as temperature increased (up to 100 C), suggesting that compounding of thermoplastics (done at higher temperatures) could lead to the release to the environment, although fugacity modeling indicated that concentrations found in outdoor air were better explained by its use as a flame retardant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, preliminary modelling results indicate that the substance is used as an additive itself (Gouteux et al 2008). Concentrations in different matrices analysed are summarized in the Table 2.11.…”
Section: Hexabromobenzene (Hbb)mentioning
confidence: 99%
“…Steady-state, nonequilibrium, level III fugacity models have been applied for both regional-scale assessment and near-field evaluation of chemical fate [8,9]. Nonequilibrium, nonsteady-state fugacity models (level IV) can account for time-varying emissions to environmental media to yield estimated recovery times for contaminated regions [10,11].…”
Section: Introductionmentioning
confidence: 99%